Sexual Assault Disclosure: Exploring the Disclosure Experiences of Women Who Have Been Sexually Assaulted - Bogaert, Holiday (Université d'Ottawa / University of Ottawa, 2024)
Sexual assault is severely underreported in today's society. Despite extensive research on sexual assault statistics and reporting rates, limited attention has been given to women's experiences of disclosure. Additionally, factors contributing to these experiences have not been highlighted. In response to this deficit, this thesis seeks to understand the experiences of women who disclose sexual assault to informal or formal support and the contexts surrounding disclosure. To do this, the following research question was answered: What ideologies and ideological assumptions, gendered norms, patriarchal norms, and violence, are present during and after women disclose their instances of sexual assault, and how does this shape their experiences of disclosure? Furthermore, what effect do these assumptions have on women's experiences of disclosure and after disclosure, change is self-perspective, lasting violence, etc.?
Keywords: Sexual assault; Rape myth; Disclosure; Ideology; Violence; Gender norms